2023
DOI: 10.1057/s41599-023-02444-w
|View full text |Cite
|
Sign up to set email alerts
|

Development of the potential of the digital economy of Russian regions through artificial intelligence humanisation

Ksenia V. Ekimova

Abstract: This paper is aimed at balancing the interests of business and society in the digital economy, to reduce the social risks of the Fourth Industrial Revolution. The goal of this paper is to study the experience and prospects of the humanisation of AI through the improvement of the practice of corporate social responsibility in Russia. By the example of the experience of Russian regions in 2021, we use econometric modelling to prove that the digital regional economy has a large potential in the sphere of humanisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…The performed literature overview revealed that there is a large number of published works on the topic of the AI economy, which is a sign of a high level of elaboration of the problem posed and a strong fundamental basis for this research. Certain aspects of the application of AI technologies in the Russian economy were developed in the works of Ekimova (2023) and Samieva et al (2023). However, the existing literature does not disclose the specifics of the Russian model of the AI economy, which remains unclear.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The performed literature overview revealed that there is a large number of published works on the topic of the AI economy, which is a sign of a high level of elaboration of the problem posed and a strong fundamental basis for this research. Certain aspects of the application of AI technologies in the Russian economy were developed in the works of Ekimova (2023) and Samieva et al (2023). However, the existing literature does not disclose the specifics of the Russian model of the AI economy, which remains unclear.…”
Section: Literature Reviewmentioning
confidence: 99%